2018
DOI: 10.12953/2177-6830/rcm.v9n1p30-36
|View full text |Cite
|
Sign up to set email alerts
|

Production of biomass and energy stock for five Eucalyptus species

Abstract: This study assessed the energy quality of different tree compartments (wood, bark, branches and leaves) for bioenergy use. Five species of the genus Eucalyptus were used, in which high heating value, contents of fixed carbon, volatile materials and ash, as well as the production of dry biomass and the amount of energy stored in each of the evaluated compartments, were measured. All evaluated species were able to produce energy, with no significant differences among species. In relation to the compartments, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…However, even though it contained the highest calorific value, the energy production in the foliage was considerably lower than stem since it had a lower accumulation of biomass. Many studies published energy production of tree species was quantified by considering the calorific value and biomass (Magnago et al, 2016;Simetti et al, 2018;Visser et al, 2020). Besides improving carbon storage, higher biomass also increased the potential of energy in tree species.…”
Section: Energy Productionmentioning
confidence: 99%
“…However, even though it contained the highest calorific value, the energy production in the foliage was considerably lower than stem since it had a lower accumulation of biomass. Many studies published energy production of tree species was quantified by considering the calorific value and biomass (Magnago et al, 2016;Simetti et al, 2018;Visser et al, 2020). Besides improving carbon storage, higher biomass also increased the potential of energy in tree species.…”
Section: Energy Productionmentioning
confidence: 99%
“…Overall, they were higher in Tibagi-PR and lower in Itaberá-SP, with values between 17.2 and 18.4 MJ kg -1 . These values are slightly lower than those of eucalyptus, from 19.3 to 20 MJ kg -1 (GUERRA et al, 2014;SIMETTI et al, 2018), and close to those observed in other materials such as sugarcane bagasse, from 17.9 MJ kg -1 to 19.4 MJ kg -1 (PAULA et al, 2011;CORREIA et al, 2020), soybean stem and pod residues, from 16.47 to 18.20 MJ kg -1 (PAULA et al, 2011;PIERRI et al, 2019) and white oat straw, from 17.9 to 18.0 MJ kg -1 (GARCÍA et al, 2012;PIERRI et al, 2019).…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, the previous studies also report that the existence of eucalyptus plantations provides a significant contribution to climate change mitigation (Magalhães et al 2020). Furthermore, a study explains that eucalyptus wood can become a potential source of renewable energy since it has a high calorific value of 4,532-4,661 kcal kg -1 (Simetti et al 2018). The use of eucalyptus wood for bioenergy has been conducted in some foreign countries, including Brazil, Spain, and Portugal, wherein the development of biomass power plants has been intensively managed (Barreiro & Tomé 2012;González-García et al 2016;Cavalett et al 2018).…”
Section: Introductionmentioning
confidence: 96%